2006
DOI: 10.1176/appi.ps.57.8.1179
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment Relationship in Peer-Based and Regular Case Management for Clients With Severe Mental Illness

Abstract: Early in treatment, peer providers may possess distinctive skills in communicating positive regard, understanding, and acceptance to clients and a facility for increasing treatment participation among the most disengaged, leading to greater motivation for further treatment and use of peer-based community services. Findings strongly suggest that peer providers serve a valued role in quickly forging therapeutic connections with persons typically considered to be among the most alienated from the health care serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 22 publications
2
115
0
3
Order By: Relevance
“…In these other projects, as in our own, peers were accepted as service providers and were seen as adding value to a professionally-led intervention with this population. The feasibility of peer delivered services for persons with serious mental illness has been previously demonstrated in supported employment (Kern et al, 2013), case management for homeless vets (Weissman, Covell, Kushner, Irwin, & Essock, 2005), case management to intensive case management (Chinman et al, 2015; Hamilton et al, 2015; Rivera, Sullivan, & Valenti, 2007) and to ACT team recipients (Sells, Davidson, Jewell, Falzer, & Rowe, 2006). There have also been previous reports of peers assisting traditional staff in promoting smoking cessation, typically as part of a broader wellness curriculum (Ashton et al, 2010; Lee et al, 2011; Williams et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In these other projects, as in our own, peers were accepted as service providers and were seen as adding value to a professionally-led intervention with this population. The feasibility of peer delivered services for persons with serious mental illness has been previously demonstrated in supported employment (Kern et al, 2013), case management for homeless vets (Weissman, Covell, Kushner, Irwin, & Essock, 2005), case management to intensive case management (Chinman et al, 2015; Hamilton et al, 2015; Rivera, Sullivan, & Valenti, 2007) and to ACT team recipients (Sells, Davidson, Jewell, Falzer, & Rowe, 2006). There have also been previous reports of peers assisting traditional staff in promoting smoking cessation, typically as part of a broader wellness curriculum (Ashton et al, 2010; Lee et al, 2011; Williams et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Walker et al [5] found, in a metasynthesis of qualitative studies on peer support, that service users experience these workers as contributing to hope regarding possibilities for recovery, expanded social networks and improved illness management skills. The peer support workers were also viewed as role models for recovery and regarded as easy to build rapport with [5,6]. Other positive outcomes suggested in the literature [4] include increases in quality of life, empowerment, functioning [7][8][9], sense of control and community belonging [10], improved social integration [5,11] and self-efficacy [12], all essential components in recovering from mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…Crane, Lepicki og Knudsen (2016) viser at det Ă„ styrke personen var den mest konkrete og unike oppgaven erfaringsmedarbeidere hadde. Sells, Davidson, Jewell, Falzer, og Rowe (2006) sammenlignet kvaliteten pĂ„ relasjoner og engasjement hos erfaringsmedarbeidere og fagpersoner. 137 brukere deltok i to forskjellige behandlingstilbud: ett med erfaringsmedarbeidere og ett uten.…”
Section: Forskjeller Mellom Erfaringsmedarbeidere Og Fagpersonerunclassified